2023
DOI: 10.1080/19490976.2023.2263936
|View full text |Cite
|
Sign up to set email alerts
|

Targeting hypoxia-inducible factor-1 alpha suppresses Helicobacter pylori -induced gastric injury via attenuation of both cag -mediated microbial virulence and proinflammatory host responses

Jennifer M. Noto,
M. Blanca Piazuelo,
Judith Romero-Gallo
et al.

Abstract: Helicobacter pylori -induced inflammation is the strongest known risk factor for gastric adenocarcinoma. Hypoxia-inducible factor-1 (HIF-1α) is a key transcriptional regulator of immunity and carcinogenesis. To examine the role of this mediator within the context of H. pylori -induced injury, we first demonstrated that HIF-1α levels were significantly increased in parallel with the severity of gastric lesions in humans. In interventional studies targeting HIF-1α, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Helicobacter pylori is a critical bacterium that infects the stomach and is a inducer of gastritis, stomach ulcers, and gastric cancer. 63,64 As mentioned previously, pinostrobin can significantly act against Helicobacter pylori activity, suggesting that pinostrobin is promising for many stomach diseases. 24 In addition, a study reported that pinostrobin protected against ethanol-induced gastric injury, as evidenced by reductions in the ulcer area, mucosal contents, submucosal edema, leukocyte infiltration, and TBARS levels in gastric homogenate.…”
Section: Multiple Organ Protectionmentioning
confidence: 81%
“…Helicobacter pylori is a critical bacterium that infects the stomach and is a inducer of gastritis, stomach ulcers, and gastric cancer. 63,64 As mentioned previously, pinostrobin can significantly act against Helicobacter pylori activity, suggesting that pinostrobin is promising for many stomach diseases. 24 In addition, a study reported that pinostrobin protected against ethanol-induced gastric injury, as evidenced by reductions in the ulcer area, mucosal contents, submucosal edema, leukocyte infiltration, and TBARS levels in gastric homogenate.…”
Section: Multiple Organ Protectionmentioning
confidence: 81%
“…Hypoxia is an important characteristic of gastric mucosal diseases, ranging from mucosal inflammatory reactions to GC. 29 , 30 PHT is indicated by a portal pressure gradient greater than 5 mmHg, namely, the difference in pressure between the portal vein and the hepatic veins, which mainly results from liver cirrhosis, 31 and PHT‐related gastric mucosal lesions are commonly defined as complications in patients with PHT. 3 And PHG and GC are the most representative benign and malignant gastric mucosal diseases characterised by hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, HIF-1α is a crucial regulator in the hypoxic microenvironment of tumors, including GC. However, two studies have shown that HIF-1α can be induced by H. pylori under normoxic conditions through reactive oxygen species or the PI3K/AKT/mTOR pathway[ 5 - 7 ], and H. pylori strains isolated from high-risk patients exert strong effects[ 8 ]. In addition, the mechanisms underlying H. pylori -induced HIF-1α expression remains unclear.…”
Section: Introductionmentioning
confidence: 99%